Perilaku Masyarakat dalam Mengonsumsi Vitamin Penambah Daya Tahan Tubuh pada Masa Pandemik Covid-19 - Niken Yufila Putri; Ridha Fitriana; Herda Ariyani (Universitas Borneo Lestari, 2022)
Corona virus will easily infect someone who has a low immune system. Consumption of vitamins is one of the measures to prevent the spread of covid 19. The purpose of this study is to know the behavior of the community in consuming vitamins during a pandemic at Apotek X. The research method is descriptive observational. Sampling by accidental sampling, the study was conducted by conducting face-to-face interviews. face uses a modified instrument from the University of Rhode Island Change Assessment. The results of this study obtained data on changes that were seen from the community at the Action stage as many as 11 people (36.66%) had made changes to their lifestyle and had prioritized vitamins as an immune booster during a pandemic. Most of the research results on vitamins that are often consumed by respondents is Vitamin C.